Oxidized cellulose mesh (Surgicel) as a biodegradable membrane in the technique of guided tissue regeneration - Felizarta, Sheila B.; Grino, Elena Marie G.
The technique of guided tissue regeneration, wherein a barrier membrane is placed under a surgical flap to prevent propagation of epithelial cell's migration apically during the healing process has been described recently. Initial membranes used were ethyl cellulose and PTFE membranes which would require secondary surgical technique because of their non-biogradability. Recently, substitutes to these materials in the form of oxidized cellulose, traditionally a hemostatic agent, have been used. A patient with 6mm. residual pocket and infrabony defect was subject to the said technique. Based on our findings after 1,2 and 4 weeks post-operatively, it has been cocluded that oxidized cellulose is an acceptable material for the procedure.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Guided tissue regeneration; Periodontal diseases